2011
DOI: 10.1190/geo2010-0399.1
|View full text |Cite
|
Sign up to set email alerts
|

Breakthrough acquisition and technologies for subsalt imaging

Abstract: The recently introduced method of wide-azimuth data acquisition offers better illumination, noise attenuation, and lower frequencies to more accurately determine a velocity field for imaging. For the field data experiment to demonstrate the technologies, we used a Gulf of Mexico (GOM) wide-azimuth data set that allows us to take advantage of possible low frequencies, relatively large crossline offsets, and increased illumination. The input data was processed through true 3D azimuthal surface-related multiple e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(19 citation statements)
references
References 22 publications
0
18
0
1
Order By: Relevance
“…In combination with the evolution of waveequation-based imaging algorithms (such as OWEM and RTM), data acquired in various wide and RAZ acquisition configurations, involving one or several vessels (e.g., RAZ, WAZ, and coiled shooting), have resulted in superior subsalt images (e.g., Vigh et al, 2011). In combination with the evolution of waveequation-based imaging algorithms (such as OWEM and RTM), data acquired in various wide and RAZ acquisition configurations, involving one or several vessels (e.g., RAZ, WAZ, and coiled shooting), have resulted in superior subsalt images (e.g., Vigh et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In combination with the evolution of waveequation-based imaging algorithms (such as OWEM and RTM), data acquired in various wide and RAZ acquisition configurations, involving one or several vessels (e.g., RAZ, WAZ, and coiled shooting), have resulted in superior subsalt images (e.g., Vigh et al, 2011). In combination with the evolution of waveequation-based imaging algorithms (such as OWEM and RTM), data acquired in various wide and RAZ acquisition configurations, involving one or several vessels (e.g., RAZ, WAZ, and coiled shooting), have resulted in superior subsalt images (e.g., Vigh et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The resulting images are significantly improved and are capable of, for example, resolving many complex subsalt plays for the first time (e.g., Vigh et al, 2011). The resulting images are significantly improved and are capable of, for example, resolving many complex subsalt plays for the first time (e.g., Vigh et al, 2011).…”
Section: Velocity Models and Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…14. Результаты WEM узкоазимутальных данных после 2D SRME (а) и RTM широкоази-мутальных данных после 3D SRME (б) [Vigh et al, 2011]. появилась возможность выявить и за-картировать положительную структу-ру на большей глубине. Эта структура в дальнейшем оказалась продуктивной.…”
Section: посвящается 90-летию со дня рождения (3 марта 1927 г) выдаюunclassified
“…Over the past few years, 3D FWI with the acoustic wave equation has been applied to real datasets in marine (Plessix, 2009, Sirgue at al., 2010, Vigh et al, 2010, 2011 and in land (Plessix, 2010) environments. These results have demonstrated that FWI can be used to update the velocity if the acquired data contain low enough frequencies and long enough offsets.…”
Section: Introductionmentioning
confidence: 99%